2015
DOI: 10.1038/ncomms9023
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a novel actin-dependent signal transducing module allows for the targeted degradation of GLI1

Abstract: The Down syndrome-associated DYRK1A kinase has been reported as a stimulator of the developmentally important Hedgehog (Hh) pathway, but cells from Down syndrome patients paradoxically display reduced Hh signaling activity. Here, we find that DYRK1A stimulates GLI transcription factor activity through phosphorylation of general nuclear localization clusters. In contrast, in vivo and in vitro experiments reveal that DYRK1A kinase can also function as an inhibitor of endogenous Hh signaling by negatively regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 62 publications
3
67
0
Order By: Relevance
“…Three sites for AMPK phosphorylation of GLI1 were identified in the medulloblastoma study; Ser 102, Ser 408 and Thr 1074. Interestingly, two of these sites were those identified by us herein (Ser408) or by others (Ser102; [40]) as DYRK1A-mediated sites on GLI1. In an independent study, phosphorylation of GLI1 by AMPK at Ser408 was shown to be inhibitory leading to GLI1 ubiquitination and proteasomal degradation [45].…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Three sites for AMPK phosphorylation of GLI1 were identified in the medulloblastoma study; Ser 102, Ser 408 and Thr 1074. Interestingly, two of these sites were those identified by us herein (Ser408) or by others (Ser102; [40]) as DYRK1A-mediated sites on GLI1. In an independent study, phosphorylation of GLI1 by AMPK at Ser408 was shown to be inhibitory leading to GLI1 ubiquitination and proteasomal degradation [45].…”
Section: Resultsmentioning
confidence: 54%
“…DYRK1A has also been shown to phosphorylate GLI1 in the N-terminal domain at two SPS clusters (S102/104 and S130/32) and that this phosphorylation promotes nuclear transport of GLI1 [40]. Further, when both SPS clusters were mutated, GLI transcriptional activity was not enhanced by DYRK1A [40]. Direct phosphorylation of Ser102 was shown by mass spectrometry [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only when calcium concentrations decrease, ERK1/2 translocate to the nucleus to regulate transcription [63]. Finally, recent studies indicate that the selectivity of the ERK1/2-NTS mechanism of stimulated nuclear import is quite specific and is used only by a few other proteins, such as MEK1/2 [32], SMAD3 [32], EGR-1 [65], GLI1 [66], Notch1 [67], and probably also Pyk2 [68] and Drosha [69]. …”
Section: The Mechanism Of Mapks Translocation Into the Nucleusmentioning
confidence: 99%